DEVELOPMENT OF ENTREPRENEURSHIP AT THE RESORT BUSINESS ENTERPRISES - Mendela, I.Ya. (The actual problems of regional economy development, 2017)
The term “entrepreneurship” is exceedingly widespread in the western management. Its essence is to provide the employee, who has a perspective idea with the possibility to use the company's resources for its implementation, thereby realizing one’s business opportunities. It can be viewed as an activity of the enterprise to achieve goals on the basis of the use of business opportunities. The partnership in the innovative activity is crucial for the effectiveness of its implementation. The partnership does not imply complete equality: professional partnership is characterized by the fact that senior ex official partners receive greater rewards and are less involved in the current work than younger counterparts. The scientific approaches concerned in developing and realization of business conception are particularly relevant in terms of overcoming the economic crisis, effective development and specialization of regional tourist and recreational complexes. The advantages of the entrepreneurship over traditional ways of tourism and recreational activities’ organization are singled out. The principles of behavior of market participants on the market of resort services are defined. The peculiarities of service enterprises are distinguished. The process of stimulating development of company entrepreneurship at resort business enterprise is considered. Based on factors of external and internal environment of business activity, differences that characterize entrepreneurship in tourism and recreation industry, trends of development, achievements of economics it was found that resort business development will stimulate entrepreneurship within the enterprise. Management system, economic indicators of business activity effectiveness, quality of service, integration, clustering, coenterprising and entrepreneurship provide realization of enterprising conception.